The epidemiology, treatment, and complication of dentofacial deformities in an Indonesian population: A 21-year analysis. Issue 5 (September 2015) - Ruslin, Muhammad; Forouzanfar, Tymour; Astuti, Ida A.; Soemantri, Eky S.; Tuinzing, Dirk B.
Abstract: Objective: The aim of the present study was to investigate the prevalence, treatment, and complication of patients with dentofacial deformities in an Indonesian cohort. Materials and methods: Study cohorts included 86 patients who were treated for dentofacial deformities with orthognathic surgery from January 1990 to December 2011. The inclusion criteria were the presence of a nonsyndromic dentofacial deformity and the exclusion criteria were facial asymmetry and cleft lip and palate. Data from each patient, including gender, age, deformity classification, surgical procedure, location of surgical procedure, and complication were reviewed and analyzed retrospectively. Results: Mandibular prognathism with an open bite was the most prevalent deformity (46.5%). Mandibular deficiency was the least prevalent deformity (2.3%). The bimaxillary surgical procedure was most frequently conducted (72.1%), bimaxillary osteotomies were performed in 95% of patients with mandibular prognathism with open bite ( P < 0.00). The most common surgical procedure to treat mandibular prognathism with an open bite was the Le Fort I osteotomy (35.8%), followed by genioplasty (28.7%), intraoral vertical ramus osteotomy (24.1%), and sagittal split osteotomy (12%) ( P < 0.00), and few complications were reported following surgery, including infection, plate exposure, mile edge-to-edge relapse, and neurosensory deficit of the inferior alveolar nerve ( P < 0.00). Conclusion: The most common deformity was mandibular prognathism with open bite, and the majority of these cases required bimaxillary osteotomies. A small number of patients exhibited complications. These present results may reflect the dentofacial deformities that are observed in Southeast Asian patients.